Exploring the Academic English Socialization of International Graduate Students in Taiwan - Lan, Shu-Wen (Journal of International Students, 2018)
Through 24 semi-structured interviews with non-native English-speaking (NNES) international graduate students, this study explores their academic English socialization experiences in Taiwan guided by Lave and Wenger’s (1991) community of practice framework and Lee and Rice’s (2007) concept of neo-racism. Throughout a complicated academic English socialization process, newcomers became increasingly competent in communicating with the university community in English. However, this process was not unproblematic; challenges included differential welcome and treatment, a relative lack of interaction with Taiwanese peers or students outside their own ethnic groups, and negative perceptions of their accents and non-fluent English. Findings suggest a need to stimulate deeper reflection on international students’ experiences in host communities, where they are increasingly the targets of nationality-based discrimination.